Double ciphertext mode: a proposal for secure backup. (1st January 2012) - Chakraborty, Debrup; Mancillas-López, Cuauhtemoc
Security of data stored in bulk storage devices like the hard disk has gained a lot of importance in the current days. Among the variety of paradigms which are available for disk encryption, low level disk encryption is well accepted because of the high security guarantees it provides. In this paper, we view the problem of disk encryption from a different direction. We explore the possibility of how one can maintain secure backups of the data, such that loss of a physical device will mean neither loss of the data nor the fact that the data gets revealed to the adversary. We propose an efficient solution to this problem through a new cryptographic scheme which we call the double ciphertext mode (DCM). In this paper, we describe the syntax of DCM, define security for it and give some efficient constructions. Moreover, we argue regarding the suitability of DCM for the secure backup application.